Non-native species and invasion biology in a megadiverse country: scientometric analysis and ecological interactions in Brazil - Frehse, Fabrício de Andrade; Braga, Raul Rennó; Nocera, Gabriel Augusto; Vitule, Jean Ricardo Simões (Biological invasions, 2016)
The number of invasions by non-native species and their negative impacts is increasing, especially in developing megadiverse countries. The current catalogue of hypotheses, concepts and management policies related to invasions was typically created and evaluated in temperate and economically rich regions. So what we know about invasion biology may not provide a general pattern applicable to developing megadiverse regions. All recent reviews have indicated a demand for more studies in tropical and megadiverse regions. Additionally, potential differences in the quality and availability of data may preclude any comparative analyses between developing and developed nations and hinder global strategies to combat invasions. Therefore, it is important to synthesize the existing knowledge on the subject in order to aid conservation activities in such regions. We conducted a systematic review of non-native species and invasions in Brazil and found geographical bias towards the most populated regions and biomes. Plants and fish were the most studied groups and were, for the most part, intentionally introduced, usually to meet some economic interest. We also noted the dominance of studies concerning terrestrial and freshwater ecosystems. Most studies did not address species interactions and, in the few cases where they did, the most frequently studied were between non-native and native species. There was a paucity of research beyond the level of species records and descriptive patterns. We highlight major vectors of introduction, the number of non-native species (proxy to colonization pressure) and papers (proxy to propagule pressure) related to each vector and the need for designed surveys and experiments focusing on specific invasion hypotheses and/or species interactions. We indicate major gaps and biases nationally that should be the focus for future studies, and that can serve as examples for other megadiverse countries.